Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.proci.2018.05.108
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-acoustic instabilities driven by fuel droplet lifetime oscillations

Abstract: OATAO is an open access repository that collects the work of some Toulouse researchers and makes it freely available over the web where possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…This motion essentially takes place in the radial direction, whereas the acoustic mode is controlled by an axial oscillation of the flow. It has recently been shown that this motion originates from droplet lifetime oscillations [26]. Figure 4a shows the heat release rate distribution _ q^η 0 without acoustic forcing (η 0).…”
Section: Simulation Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…This motion essentially takes place in the radial direction, whereas the acoustic mode is controlled by an axial oscillation of the flow. It has recently been shown that this motion originates from droplet lifetime oscillations [26]. Figure 4a shows the heat release rate distribution _ q^η 0 without acoustic forcing (η 0).…”
Section: Simulation Resultsmentioning
confidence: 93%
“…The oscillation level chosen to excite the system corresponds to half the pressure level observed at the limit cycle of unstable cases studied in Refs. [25,26], and the selected forcing frequency is defined by the frequency of the limit cycle of a close unstable case [25,26] of D r 60 μm.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 3 more Smart Citations